Relationship between official visits, industry chain coordination and digital transformation in China - Yonghao Jiang; Bei Lyu (Heliyon)
With digital transformation becoming a global consensus, governments around the world are vigorously promoting the implementation of enterprise digital transformation. However, there are some uncertainties in the process of digital transformation, and companies have overlooked the role of formal access. To better understand the role official visits play in digital transformation, based on signal theory, the study examines the influence of official visits on corporate digitalization using data from listed SMEs in China from 2017 to 2021. Our study found that Official visits are positively correlated with the digital transformation of SMEs; the coordination of the industrial chain plays a partial mediating role in the positive relationship between official visits and the digital transformation of SMEs; the pressure of official promotion positively moderates the impact of official visits on the digital transformation of small and medium-sized enterprises. As a signaling party, this is because the government will enhance the signal strength that firms will receive resources to shelter and further reduce the risk of digitalization strategies. Based on the perspective of signal theory, the study investigates the underlying mechanism of official visits influencing digital transformation through industry chain coordination, which expands the relevant literature on political connections and digital transformation.